Dietary inclusion of curry plant (Helichrysum italicum) extract in rainbow trout (Oncorhynchus mykiss) culture: Growth performance and gene expression related to digestion, antioxidant, and immune responses - Ayşegül Aydın; Dogukan Kaya; Boran Karataş; Derya Guroy (Journal of the World Aquaculture Society, 2025)
Abstract In this study, a 60‐day trial was conducted to determine the effects of curry plant (Helichrysum italicum) extract in the diet of rainbow trout (Oncorhynchus mykiss) with an initial average live weight of 15.84 ± 0.05 g on growth performance and gene expressions associated with digestion, antioxidant capacity, and immune response. Four experimental diets were formulated as a basal diet (Control; C) and diets supplemented with varying levels of curry plant extract (CP05; 0.5 g kg−1, CP1; 1 g kg−1, and CP2; 2 g kg−1). Growth indices showed significant increases in all curry plant extract groups compared to the C group (p < 0.05). Similarly, higher levels of trypsin, lipase, and amylase expressions were observed in the curry plant extract groups compared to the C group (p < 0.05). The superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) gene expression levels were elevated in the CP extract groups (p < 0.05). The expression levels of interleukin‐1β (IL‐1β), tumor necrosis factor (TNF‐α), and interleukin‐8 (IL‐8) were also influenced by the incorporation of CP extract into the diet, showing significant changes (p < 0.05). In conclusion, this study experimentally demonstrates that supplementing the diet of rainbow trout with CP extract can positively influence healthy growth parameters.